Coronary artery disease detected by coronary computed tomography angiography is associated with red cell distribution width - Emir Karaçağlar; Ugur Bal; Senem Hasırcı; Mustafa Yılmaz; Ersin Doganözü; Mehmet Coskun; İlyas Atar; Aylin Yıldırır; Haldun Muderrisoglu (KARE Publishing, 2016)
Objective: Increased red blood cell distribution width (RDW) is associated with severity of coronary artery disease (CAD). The aim of the present study was to retrospectively evaluate the relationship between CAD detected by coronary computed tomography angiography (CCTA) and RDW. Methods: Records of 291 patients who underwent 16-slice CCTA due to the presence of angina-like chest pain were retrospectively evaluated. Exclusion criteria were applied. Clinical characteristics, risk factors for CAD, and RDW values on CCTA were noted. Results: RDW levels in patients with CAD were significantly higher than in those with normal coronary arteries (NCAs) (15.50+-1.57 compared to 14.80+-1.41, p=0.001). Diabetes mellitus, hypertension, and history of smoking were significantly more common in the CAD group (p=0.018, p=0.007, and p=0.013, respectively). On multivariate logistic regression analysis, RDW (p=0.009 [odds ratio (OR): 1.352; 95% confidence interval (CI): 1.081-1.683]), age (p<0.001 [OR: 1.063; 95% CI 1.031-1.090]), and history of smoking (p=0.003 [OR: 2.672; 95% CI: 1.360-5.232]) were shown to be independent predictors for CAD detected by CCTA. Conclusion: The present results suggest that higher RDW levels are independently associated with presence of CAD detected by CCTA in patients without known CAD. Further studies are warranted to clarify the exact role of RDW in risk stratification.